2009
DOI: 10.2478/s11534-008-0150-x
|View full text |Cite
|
Sign up to set email alerts
|

The q-exponential family in statistical physics

Abstract: Abstract:The notion of a generalized exponential family is considered in the restricted context of non-extensive statistical physics. Examples are given of models belonging to this family. In particular, the -Gaussians are discussed and it is shown that the configurational probability distributions of the micro-canonical ensemble belong to the -exponential family.PACS (2008)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 47 publications
0
60
0
Order By: Relevance
“…This is the q-Gibbs distribution or q-exponential family [4], which we denote by S, where the domain of x is restricted such that p(x, θ) > 0 holds. The function ψ q (θ), called the q-free energy or q-potential function, is determined from the normalization condition:…”
Section: Q-exponential Familymentioning
confidence: 99%
See 2 more Smart Citations
“…This is the q-Gibbs distribution or q-exponential family [4], which we denote by S, where the domain of x is restricted such that p(x, θ) > 0 holds. The function ψ q (θ), called the q-free energy or q-potential function, is determined from the normalization condition:…”
Section: Q-exponential Familymentioning
confidence: 99%
“…The function ψ q depends on q, but we hereafter neglect suffix q in most cases. Research on the q-exponential family can be found, for example, in [2,4,19]. The q-Gaussian distribution is given by…”
Section: Q-exponential Familymentioning
confidence: 99%
See 1 more Smart Citation
“…We discuss a typical example by the power entropy H β (f ), see [15,[30][31][32][33][34]] from a viewpoint of statistical physics. First we consider a mean equal space of univariate distributions on (0, ∞)…”
Section: Maximum Entropy Distributionmentioning
confidence: 99%
“…For example, the family not only describes phenomena obeying the power-law well [6], but also, it is theoretically proven to include a velocity distribution of the classical gas with N particles [9,10], an attracting invariant manifold of porous media flow [11], and so on. In statistics, it is reported to provide a reasonable statistical model in robust inference from data losing normality [1,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%